Collaboration between Vocational Higher Education and UMKM Towards National Empowerement: Kolaborasi Perguruan Tinggi Vokasi dan UMKM menuju Kemandirian Nasional - Hapsari, Ratih Indri; Adhisuwignjo, Supriatna; Alia*, Nila; Perdana, Fengky Adie; Kusmintarti, Anik; Melani, Erlin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Micro, Small, and Medium Enterprises/UMKM are one of the main pillars of economic fundamentals that contribute positively to the Indonesian economic ecosystem. However, the high role of UMKM in the Indonesian economy is still hindered by the large number of UMKM in the informal sector, making it difficult to upgrade. The purpose of this community services activity is to increase the empowerement of UMKM actors through mentoring activities by vocational college collaborated with KADIN Malang City and Jawa Timur province and BUMDes in Malang Regency. The UMKM mentoring method is carried out with lectures, discussions, questions and answers, training and assignments, as well as direct output-based assistance. The results of PkM activities show that UMKM assistance from lecturers as well as students provides solutions to partner problems related to aspects of management, legality, capital, and UMKM resilience strategies, as well as increasing independence, adding knowledge and business skills improvement